Modeling Tephra Fall and Sediment-Water Flows to Assess Their Impacts on a Vulnerable Building Stock in the City of Arequipa, Peru - Thouret, J.-C.; Arapa, E.; Charbonnier, S.; Guerrero, A.; Kelfoun, K.; Cordoba, G.; Rodriguez, D.; Santoni, O. (Frontiers in Earth Science, 2022)
Arequipa, Peru’s second economic center hosting c. 1,110,000 inhabitants, is the largest South American city exposed to a large variety of natural hazards. At least 200,000 live in areas likely to be affected by hazards from El Misti volcano, located 17 km to the NE. A multidisciplinary project aims to address the impacts of tephra fall and frequent mass flows on the vulnerable building stock and roofs along two ravines that cross the city, enabling decision-makers to undertake retrofitting projects and improve urban risk planning. Two recent eruptions, that is, the 1440–1470 CE Vulcanian event and c. 2070 years BP Plinian eruption, were chosen as references for probable scenarios of potential tephra fall impacts from El Misti on the building roofs. Tephra fall impacts on the city depend on the eruptive style, column height, and patterns of wind directions and velocities over south Peru and roof mechanical resistance. Estimates of potential damage levels and cost range values rely on nine structural types and four classes of vulnerable roofs. Simulation runs of hyperconcentrated flows (HCF) and debris flows (DF), using three depth-averaged flow models (Titan2F, VolcFlow, and Flo-2D) along two drainage basins on the SW flank of El Misti and across Arequipa, examined three scenarios from a database of 39 recent events and other historical lahars. Simulation results showcase the extent toward the city, inundation depths ≤4.6 m, flow velocities ≤9 m/s, and dynamic pressure up to 100 kPa from three different magnitude HCFs and DFs. In both ravines, overbank flows occurred in key urban areas due to channel sinuosity and constrictions near bridges. Potential impacts on habitat stem from ranges of flow dynamic pressure and measurements of construction material. We estimated the monetary loss of buildings according to hyperconcentrated flows and debris flows scenarios to contribute to retrofitting procedure, implementation of defense work, and relocation policy.